2011
DOI: 10.1089/tmj.2010.0164
|View full text |Cite
|
Sign up to set email alerts
|

Text Messaging for Enhancement of Testing and Treatment for Tuberculosis, Human Immunodeficiency Virus, and Syphilis: A Survey of Attitudes Toward Cellular Phones and Healthcare

Abstract: Objectives: The objective of this study was to assess knowledge, attitudes, and behaviors surrounding healthcare-related mobile phone use and text messaging among persons at risk for or infected with tuberculosis (TB) or the human immunodeficiency virus (HIV). Methods: An anonymous survey was conducted in three groups of subjects: (1) HIV-infected persons attending an HIV clinic; (2) persons with latent TB infection at a public health clinic; and (3) persons presenting for TB, HIV, and syphilis screening at a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 18 publications
3
49
1
1
Order By: Relevance
“…8 Our study also confirmed the finding that patients are more receptive to receiving medication 'reminders' than general medical education via text-message. 8 Nonresponse to the outgoing text messages approximated that of the original WelTelKenya1 trial, 9 and similarly, a low proportion of patients responded with a problem. Other mHealth interventions to improve adherence to TB treatment are also being explored.…”
Section: Discussionsupporting
confidence: 85%
“…8 Our study also confirmed the finding that patients are more receptive to receiving medication 'reminders' than general medical education via text-message. 8 Nonresponse to the outgoing text messages approximated that of the original WelTelKenya1 trial, 9 and similarly, a low proportion of patients responded with a problem. Other mHealth interventions to improve adherence to TB treatment are also being explored.…”
Section: Discussionsupporting
confidence: 85%
“…In regard to rigor, mHealth HIV self-management science is in the early stages of development, with most of the published work being exploratory rather than experimental (Chander et al, 2012;Person, Blain, Jiang, Rasmussen, & Stout, 2011;Ramanathan et al, 2013). In fact, many of the published studies did not meet our criteria for inclusion because they were cross-sectional and/or qualitative in nature.…”
Section: Discussionmentioning
confidence: 99%
“…The intervention group also had higher awareness of sexual health compared to the controls. Another study found that young persons have positive attitudes toward text messages as appointment or medication reminders or for health information related to HIV (Person, Blain, Jiang, Rasmussen, & Stout, 2011). Receiving a text message was perceived as more acceptable than having to answer the phone.…”
Section: Wwwintechopencommentioning
confidence: 99%